Cerebrovascular Complication and Valve Surgery in Infective Endocarditis - Rice, Cory J.; Kovi, Shivakrishna; Wisco, Dolora R. (Seminars in Neurology, 2021)
Infective endocarditis (IE) with neurologic complications is common in patients with active IE. The most common and feared neurological complication of left-sided IE is cerebrovascular, from septic emboli causing ischemic stroke, intracranial hemorrhage (ICH), or an infectious intracranial aneurysm with or without rupture. In patients with cerebrovascular complications, valve replacement surgery is often delayed for concern of further neurological worsening. However, in circumstances when an indication for valve surgery to treat IE is present, the benefits of early surgical treatment may outweigh the potential neurologic deterioration. Furthermore, valve surgery has been associated with lower in-hospital mortality than medical therapy with intravenous antibiotics alone. Early valve surgery can be performed within 7 days of transient ischemic attack or asymptomatic stroke when medically indicated. Timing of valve surgery for IE after symptomatic medium or large symptomatic ischemic stroke or ICH remains challenging, and current data in the literature are conflicting about the risks and benefits. A delay of 2 to 4 weeks from the time of the cerebrovascular event is often recommended, balancing the risks and benefits of surgery. The range of timing of valve surgery varies depending on the clinical scenario, and is best determined by a multidisciplinary decision between cardiothoracic surgeons, cardiologists, infectious disease experts, and vascular neurologists in an experienced referral center.
Keywords: infective endocarditis; cerebrovascular complications; valve surgery; cerebral microbleed; stroke